MAKANAN DAN KEBIASAAN MAKAN IKAN GEROT Pomadasys kaakan (CUVIER & VALENCIENNES,1830) DI TELUK PABEAN JAWA BARAT - Chilmia Ayu Annisa; M Fadjar Raharjo; Ahmad Zahid; Charles P.H Simanjuntak; Aries Asriansyah; Reiza M Aditriawan (Jurnal Perikanan Universitas Gadjah Mada, 2018)
The Pabean Bay is an estuary area that inhabited by many fish species such as javelin grunt (Pomadasys kaakan Cuvier, 1830). The purposes of this study were to identify food item and determine the feeding habit of the javelin grunt in The Pabean Bay, West Java. Fishes were collected monthly from June to December 2016 using gill nets and trap nets. Observation food is in vitro by conducting an examination of the stomach and the intestines of an example and refer on the books of the identification by Carpenter and Niem. Analysis of fish diet includes index of relative importance, niche breadth, and niche overlap. Fishes were grouped into three groups based on the size length. The result showed that the javelin grunt was crustacivore. Generally, the diet of javelin grunt consists of Acetes sp., Penaeus sp., Portunus sp., Clupeid, Ambassid, Sciaenid, Gobiid, Sillaginid, and unidentified organisms. Penaeus sp. was the main food and could be found on each size of group in monthly observation. The proportion of index of relative importance value was changed in regard of length size groups of A (41-85 mm: 12.105), B (86-130 mm: 13.804), and C (131-175 mm: 7.561). The niche breadth of javelin fish was higher in the larger ones and a high diet overlap among size groups was found. According to prey item and feeding habit, the javelin grunt can be classified as benthic crustacean feeder.